2022
DOI: 10.5435/jaaos-d-22-00072
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Patients With Primary Osseous Malignancies of the Mobile Spine Is Associated With Access to “Standard Treatment” Protocols

Abstract: Introduction:Malignancies of the mobile spine carry high morbidity and mortality. This study sought to examine factors associated with receipt of “standard” treatment and survival for patients with primary mobile spine tumors in the California Cancer Registry (CCR).Methods:The CCR (1988 to 2016) data were obtained for patients with primary tumors of the mobile spine and at least 1-year follow-up. Sacrum/pelvis tumors were excluded. Age at diagnosis, sex, race, neighborhood socioeconomic status, insurance, Char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…However, the authors found that surgical resection was beneficial in preventing new neurologic deficits. Similarly, through the California Cancer Registry, Stroud et al evaluated patients with primary bone malignancies of the mobile spine 29 . Patients who underwent standard treatment had lower mortality rates when compared with patients who did not undergo any known treatment.…”
Section: Bone Tumorsmentioning
confidence: 99%
“…However, the authors found that surgical resection was beneficial in preventing new neurologic deficits. Similarly, through the California Cancer Registry, Stroud et al evaluated patients with primary bone malignancies of the mobile spine 29 . Patients who underwent standard treatment had lower mortality rates when compared with patients who did not undergo any known treatment.…”
Section: Bone Tumorsmentioning
confidence: 99%
“…The National Cancer Institute’s Surveillance, Epidemiology, and End Results (SEER) database, the American College of Surgeons (ACS) National Cancer Database, and the California Cancer Registry were queried by several authors who concluded that radiation therapy is the most common local modality used in the United States for Ewing sarcoma of the sacrum or pelvis and has similar efficacy to surgical resection with or without radiation therapy; that 5-year disease-specific survival in patients with mobile vertebral column sarcomas was 56%, with worse survival for osteosarcoma; and that patients with malignancies of the mobile spine with public insurance are vulnerable to worse outcomes, even if they receive standard treatment 6,9,11 .…”
Section: Primary Bone Tumorsmentioning
confidence: 99%
“…A few studies have identified risk factors for poorer oncologic and surgical outcomes in pelvic tumors. These include a venous tumor thrombus, a margin of <2 mm, complete acetabular resection compared with transacetabular resection, and sarcopenia 1,3,7,8 .The National Cancer Institute's Surveillance, Epidemiology, and End Results (SEER) database, the American College of Surgeons (ACS) National Cancer Database, and the California Cancer Registry were queried by several authors who concluded that radiation therapy is the most common local modality used in the United States for Ewing sarcoma of the sacrum or pelvis and has similar efficacy to surgical resection with or without radiation therapy; that 5-year disease-specific survival in patients with mobile vertebral column sarcomas was 56%, with worse survival for osteosarcoma; and that patients with malignancies of the mobile spine with public insurance are vulnerable to worse outcomes, even if they receive standard treatment 6,9,11 .Disclosure: The Disclosure of Potential Conflicts of Interest forms are provided with the online version of the article (http://links.lww.com/JBJS/H270).…”
mentioning
confidence: 99%